Editorial policy and sigla (EPAS_II_XXXIII) - Robinson, James M. (BrillOnline Reference Works, 2012)
Parallel or equivalent Coptic texts of all four manuscripts and of all three English translations are placed, wherever possible, on the same line. Any given Synopsis double page and line number refers thus to seven items simultaneously: to parallel text in the four Coptic manuscripts and to the corresponding English translations. The placement of the English translations is less precise, since English syntax does not always allow a one-to-one alignment of sense-lines with the Coptic. The user should consult the Coptic lines for precise references to the Synopsis. Blank space has been left when one of the versions has no parallel text. When text is missing due to a lacuna or missing pages in a manuscript, the corresponding lines in the synopsis are marked with three dots "...". Strokes, articulation marks and punctuation have not been reconstructed. Strokes have been added to reconstructed text only when they are visible. Coptic page numbers of the manuscripts are listed in the introduction